2023
DOI: 10.3390/molecules28072915
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits the Progression of Osteoarthritis by Mediating Macrophage Polarization

Abstract: Objective: The overall purpose of this study was to investigate the mechanism of macrophage polarization on chondrocyte injury in osteoarthritis and the protective effect of apigenin on chondrocytes in osteoarthritis. Method: Primary chondrocytes were isolated from the knee cartilage of three-day-old mice, and cells positive for Alsine blue staining and type II collagen immunocytochemical staining were identified and used in followup experiments. Transwell coculture was performed. Chondrocytes were inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…IL‐1β and IL‐6 are crucial inflammatory mediators released by M1 macrophages and are involved in the degeneration of joint cartilage. [ 25 ] To investigate whether NP@Poly RHAPM might restrict the release of inflammatory mediators in M1 macrophages, the levels of IL‐1β and IL‐6 in cell supernatants were measured using an enzyme‐linked immunosorbent assay (ELISA). The results demonstrated that IL‐1β and IL‐6 were significantly generated by M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…IL‐1β and IL‐6 are crucial inflammatory mediators released by M1 macrophages and are involved in the degeneration of joint cartilage. [ 25 ] To investigate whether NP@Poly RHAPM might restrict the release of inflammatory mediators in M1 macrophages, the levels of IL‐1β and IL‐6 in cell supernatants were measured using an enzyme‐linked immunosorbent assay (ELISA). The results demonstrated that IL‐1β and IL‐6 were significantly generated by M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…There is research that found that cis-resveratrol could reduce inflammation by inhibiting canonical and non-canonical inflammasomes in macrophages ( Huang et al, 2014 ). Apigenin alleviates macrophage-polarization-induced inflammatory response ( Ji et al, 2023 ). Apigenin has been shown to exert anti-inflammatory activity ( Ouyang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells in each group were collected, total RNA was extracted by an RNA isolation and extraction kit, the RNA was reverse transcribed into cDNA by a reverse transcription kit, the housekeeping gene GAPDH was selected as an internal reference, and real-time fluorescence quantitative PCR was performed by using SYBR® GreenERTM SuperMix Universal (Invitrogen®) [ 30 ]. Relative expression was calculated by the 2-ΔΔCt method (ΔCt is the difference between the threshold cycle of the samples and the reference value of GAPDH), and the sequences of the primers used in the experiment are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%